ANALISIS KEUNTUNGAN PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP USAHA KULINER DI KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA (PROFIT ANALYSIS OF USING INFORMATION AND TECHNOLOGY ON CULINARY BUSINESS IN THE KAUDITAN SUB DISTRICT OF NORTH MINAHASA DISTRICT) - Adelina Velti Mokolensang; Lyndon Reindhart Jacob Pangemanan; Sherly Gladys Jocom (Sam Ratulangi University, 2021)
This study aims to analyze the advantages of information technology on culinary business in Kauditan District, North Minahasa Regency. This research was conducted from December 2019 to March 2020 with the object of research is culinary businesses that use information technology, especially social media. The data used in this study are primary data and secondary data. Primary data was obtained from interviews to respondents of culinary business owners using questionnaires while secondary data was obtained from parties related to this research. Sample determination method is using Simple Random Sampling method. Data collection of respondents are culinary business owners who have used Information Technology. The results showed that all respondents (as many as 30) experienced an increase in profits after using information technology.